Constitucionalismo regional transformador, Sistema Interamericano e a proteção dos Direitos Econômicos, Sociais, Culturais e Ambientais (DESCA) na América Latina - Ignácio, Renata Rossi (2020)
This study aims to overcome the classic conception of constitutional hierarchy to think about a heterarchical model, considering the global reality in which we are inserted. Global problems demand global responses, and the judicial ambit needs to adapt to provide more protective solutions to individuals. The Ius Constitutionale Commune in Latin America is based on the transformative constitutionalism to seek standards that concretize the pro persona principle, focusing on the most unequal region on the planet: Latin America. It was analyzed the international standards and the necessity to apply them in the region for the effectiveness of human rights. Latin America is characterized mainly by profound socio-economic inequality, a historical pattern of discrimination against vulnerable groups, and dilemmas of democratic institutionality. The Constitutions of the region, despite providing a wide range of fundamental rights, do not have a history of implementing these rights. In particular, I highlighted the economic, social, cultural, and environmental rights (ESCER) since that, for these to be effective, it is crucial an articulation between different actors, both national and international. Considering the universality, indivisibility, and interrelationship of human rights, the ESCER have gained significant importance in recent years for international jurisprudence, especially from the Inter-American Court of Human Rights. It was fundamental to analyze the standards about the ESCER, the Ius Commune theory and the impact of the Inter-American System as a way to protect and promote them, to understand the importance of the dialogical relationship between national and international Courts. I argue that it is necessary to create a new order, more democratic, multidisciplinary, and egalitarian, capable of guaranteeing human rights through legal, administrative, and legislative mechanisms, based on regional and global systems' standards